2014
DOI: 10.1111/pai.12198
|View full text |Cite
|
Sign up to set email alerts
|

Severe childhood asthma and allergy to furry animals: Refined assessment using molecular‐based allergy diagnostics

Abstract: Children with severe allergic asthma had higher sIgE levels to cat, dog and horse. Molecular-based allergy diagnostics revealed a more complex molecular spreading of allergen components in children with the most severe disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
106
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(121 citation statements)
references
References 28 publications
11
106
0
4
Order By: Relevance
“…Fel d 4-specific IgEs were found in 39% of serum samples from cat-allergic patients. This results are in a well agreement with 34% of Fel d4 positive samples obtained in 2014 years study (Konradsen et al 2014) and differ from another study in which the percentage of patients sensitized to Fel d 4 reached 63% (Smith et al 2004). Differences in IgE binding could be caused by various factors.…”
Section: Discussionsupporting
confidence: 70%
“…Fel d 4-specific IgEs were found in 39% of serum samples from cat-allergic patients. This results are in a well agreement with 34% of Fel d4 positive samples obtained in 2014 years study (Konradsen et al 2014) and differ from another study in which the percentage of patients sensitized to Fel d 4 reached 63% (Smith et al 2004). Differences in IgE binding could be caused by various factors.…”
Section: Discussionsupporting
confidence: 70%
“…Specific IgE to Can f 2 was significantly associated with asthma diagnosis, Can f 3 with moderate/severe rhinitis and asthma diagnosis, Can f 5 with persistent and moderate-severe rhinitis, and Equ c 3 with persistent rhinitis and severe asthma [64]. Furthermore, the sensitization to Can f 2 and Equ c 1 was more common in severe asthma than in children with controlled asthma [65]. Asthmatic children with cat allergy have higher Fel d 1-specific IgE levels as compared to those with rhinitis alone, and this suggests that high IgE levels to Fel d 1 could be a marker of increased asthma risk [66].…”
Section: Animal Dander Sensitization and Severe Asthmamentioning
confidence: 99%
“…It has recently been reported that CRD may improve the assessment of asthma (31,43) and help better understanding the role of allergy in severe asthma in childhood (44). However, it is likely that better interpretation algorithms are needed to capitalize fully on the potential of this exciting new technology (43).…”
Section: Component-resolved Diagnostics In Asthmamentioning
confidence: 99%